Selective cis-dihydroxylation of olefins using recyclable homogeneous molybdenum acetylide catalyst - Biradar, Ankush V.; Sathe, Bhaskar R.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Journal of Molecular Catalysis A-Chemical, 2008)
Selective cis-dihydroxylation of various olefins has been carried out using molybdenum acetylide complex CpMO(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as an efficient and environmentally benign oxidant. In case of cyclohexene, very high conversion (95%) and selectivity (86%) for cis-dihydroxylated product has been achieved using H2O2 as an oxidant and t-butanol as a solvent. cis-Dihydroxylation of other substrates like styrene, a-methyl styrene, limonene and cyclopentene has also been carried out with very high selectivity for diol. The catalyst and intermediate species have been characterized using FT-IR, UV-vis spectral analysis and XPS studies as well as cyclic voltametric studies. These studies suggest that molybdenum oxo-peroxo complex is the catalytically active species. The intermediate blue complex when characterized by ESI MS suggested the formation of dimeric molybdenum complex and XPS and cyclic voltametric studies confirm the presence of mixed valence Mo(V) and Mo(VI) in the reaction intermediate. Based on the characterization results possible mechanism for dihydroxylation is proposed. Interestingly, even though the catalyst is homogeneous; it could be recovered quantitatively by extraction in aqueous phase and recycled five times without any appreciable loss in cyclohexene conversion and selectivity for cis-1,2-cyclohexanediol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: acetylide complex; cis-dihydroxylation; Homogeneous catalysis; Hydrogen peroxide; recyclable

Manganese incorporated on glucose as an efficient catalyst for the synthesis of adipic acid using molecular O2 in aqueous medium - Nale, S.D. (Applied Catalysis A: General, 2017)
A new manganese incorporated on glucose catalyst Mn@CC-SO3H-NH2 was synthesized and well characterized using FT-IR, PXRD, EDAX, SEM, TEM, [13] C cross-polarization NMR and BET analysis. The catalyst thus synthesized was studied for its utility in the synthesis of industrially important chemical adipic acid starting from readily available cyclohexanone using molecular O2 as a source. Adipic acid was obtained in maximum yield of 82% using Mn@CC-SO3H-NH2 catalyst in water as a solvent. The catalyst was easily recovered and reused for minimum five runs without any significant loss in the yield of products. Using molecular O2 as an oxidant and water as a solvent, the reaction is very important from green chemistry perspectives and can also be industrially feasible.
Keywords: Adipic Acid; Catalyst; manganese; recyclable; Water

CuNPs@Al2O3-cellulose composite for the ligand-free Suzuki cross-coupling reactions in batch and continuous flow process - Patil, Seema; Rajmane, Archana; Jadhav, Sanjay; Rode, Chandrashekhar; Kumbhar, Arjun (Journal of Organometallic Chemistry, 2024)
In the present work, we synthesized recyclable CuNPs@Al2O3-CELL composite from an inexpensive and commercially available synthetic reagent by a simple method. The catalyst was characterized by various techniques such as TGA (Thermogravimetric analysis), SEM (Scanning electron microscope), TEM (Transmission electron microscopy), XPS (X-ray photoelectron spectroscopy), EDS (Energy dispersive spectroscopy), and AAS (Atomic Absorption Spectroscopy). The composite was applied for the Suzuki coupling reactions in the batch and flow process. The aryl halides were easily coupled with arylboronic acids in 95 % ethanol at 78 C. We systematically investigated the role of reaction temperature, solvent, and catalyst loading, on the transient and steady-state behavior of the flow reactor through an automated flow chemistry platform. The CuNPs@Al2O3CELL catalytic particles demonstrate minimal deactivation and leaching over a continuous Suzuki coupling reaction at a 20 min nominal residence time at 100 C. Moreover, the catalyst can be recovered by simple filtration and reused at least five times with a moderate decrease in product yield. The excellent activity and stability of the catalyst have been attributed to the strong chelation of the Cu species with hydroxyl functional groups of the Al2O3-CELL composite. The catalytic system was highly efficient in Suzuki coupling of various aryl bromides with different aryl boronic acids, yielding good to excellent product yields (80-96 %) with a TON of 15.914-19.066 and TOF of 2.649-9.533 h(-1).
Keywords: Continuous flow process; CuNPs@Al2O3-CELL; ligand-free; recyclable; Suzuki coupling